MISSING CHILD IDENTIFICATION USING DEEP LEARNING AND MULTICLASS SVM-ACCESS - Mrs.B.Prathibha,D.Sreelatha, G.Jahnavi, N.Bhavana, D.Sai priya (Pegem Journal of Education and Instruction, 2023)
In India, a critical number of kids disappear every year, with many cases staying unsettled. This paper presents an inventive profound learning way to deal with recognize missing youngsters utilizing face acknowledgment innovation. The proposed framework permits people in general to transfer photographs of kids they suspect may miss, alongside milestones and comments. These transferred pictures are then naturally contrasted with a data set of enrolled missing youngster photographs.